Religious Moderation in the Era of Ali ibn Abi Talib’s Leadership - Wahid, Abdurrohim; Nasor, M.; Basyar, Syaripudin (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Religious moderation referred to a middle-path principle that upheld balance, justice, and tolerance in religious life. This study aimed to describe the implementation of religious moderation values during the leadership of Caliph Ali ibn Abi Talib, who was known as a visionary leader in facing early Islamic social, political, and religious challenges. This research employed a qualitative approach with a library research design and content analysis of relevant primary, secondary, and tertiary sources. The findings revealed that values such as justice, equality, nonviolence, tolerance, life balance, and deliberation were strongly reflected in various aspects of Ali’s leadership, including legal practices, governance, social relations, state policy, and scholarly contributions in the field of Islamic jurisprudence (fiqh). Narratives such as the dispute over war armor with a Christian citizen, the fair resolution of a bread-sharing conflict, and a humanistic leadership approach illustrated Ali’s strong commitment to moderation. The implications suggested that Ali ibn Abi Talib’s exemplary leadership remained relevant as a character education model, particularly in strengthening religious moderation in contemporary Islamic education. This research provided a deep historical perspective and encouraged the integration of moderate values into contextual and reflective Islamic Religious Education.